A Comparison of Epidural Anesthesia without Motor Block Versus General Anesthesia for Percutaneous Nephrolithotomy - Sedat Öner; Burak Acar; Efe Önen; Metin Kılıç; Mustafa Murat Aydos; Murat Demirbaş; Ali Ekber Yürekli (Journal of Urological Surgery, 2018)

(untitled)
Objective:The study carried out to compare the operative parameters and stone clearance in patients who underwent percutaneous nephrolithotomy (PNL) under epidural anesthesia (EA) without motor block versus those who underwent PNL under general anesthesia (GA).Materials and Methods:We retrospectively reviewed 2 groups of patients who underwent PNL at our institute between January 2014 and September 2014. Group 1 consisted of 69 consecutive patients who underwent PNL under EA without motor block and group 2 consisted of 69 consecutive patients who underwent PNL under GA. Patients general characteristics, stone features, surgical parameters, duration of surgery, time spent in the operating room, postoperative analgesic requirements, complications, stone clearance rate and mean length of hospital stay were compared between the 2 groups.Results:The two groups were similar in terms of mean age, gender, stone size and previous surgery. Operative time, access site, mean access number, postoperative fever, drainage, mean hemoglobin drop, stone-free rate, duration of nephrostomy tube and length of hospitalization were also similar between the groups. The time spent in the operating room, blood transfusion rate and postoperative analgesic requirements in EA group were significantly lower than those in GA group.Conclusion:PNL under EA without motor block is as effective and safe as PNL under GA and it offers some advantages as with lower parenteral analgesic requirements, lower transfusion rates and lesser usage of operation room.